Positive effects of Mulberry leaf extract on egg quality, lipid metabolism, serum biochemistry, and antioxidant indices of laying hens - Zhang, Bo; Wang, Zeben; Huang, Chenxuan; Wang, Dehe; Chang, Dongmei; Shi, Xiaowei; Chen, Yifan; Chen, Hui (Frontiers in Veterinary Science, 2022)
This study investigated the effects of adding mulberry leaf extract (MLE) to the diet on egg quality, lipid metabolism, serum biochemistry and antioxidant indexes of laying hens. A total of 288 Lohmann Silber layers aged 38 wk were randomly assigned into 4 groups (6 replicates of 12 hens each). Hens were fed the basal diet supplemented with 0% (control diet), 0.4%, 0.8% or 1.2% MLE for 56 d.The results showed that the addition of 0.4~1.2% MLE to the diet increased the serum glutamic oxaloacetic transaminase (AST) activity and decreased the Low-Density Lipoprotein (LDL-C) content and the yolk triglyceride (TG) and total cholesterol (TC) contents were also significantly decreased (p < 0.05). 0.4% and 1.2% MLE significantly reduced TG and TC in the liver (p < 0.05). 0.8% and 1.2% MLE significantly increased serum glutathione peroxidase (GSH-Px) and glutathione alanine transaminase (ALT) activities, reduced TG and TC, and increased egg yolk color to some extent (p < 0.05). 1.2% MLE significantly increased serum high-density lipoprotein (HDL-C) content, superoxide dismutase (SOD) activity and eggshell strength (p < 0.05). The liver-related lipid metabolism gene assay revealed that the relative mRNA expression of PPARα and SIRT1 in the liver was significantly up-regulated, and that of FASN and PPARγ was significantly decreased after the addition of MLE, while the relative mRNA expression of SREBP-1c in the liver was dramatically decreased after the addition of 0.8% and 1.2% MLE (p < 0.05). Generally speaking, adding MLE to the diet improved egg quality and the economic value of the hens by increasing antioxidant capacity and lipid metabolism. The most appropriate amount of MLE to be added to the diet of laying hens is 0.8% to 1.2%.